Comprendamos el tiempo que tom el proceso de hominizacin - Silvestre Gutirrez, Willam Nilson (2019)
The title of this learning session is: Lets understand the time taken by the hominization process" which is designed for the First Grade of the Secondary Level corresponding to the area of Science Social. The first part for the planning of the class session considers competence, capacity, learning evidence and the evaluation. In the didactic sequence all the pedagogical and didactic processes in the area are considered. The competition is Build Historical Interpretations, in which it allows students to develop critical position on historical facts and processes to help them understand the present articulating the analysis and synthesis of various sources of information. Various learning activities will be carried out to achieve the purpose of the session. The second part discusses the process of man's origin, the process of hominization or evolution of human beings and the characteristics of each process. The third part considers pedagogical sustenance, here we talk about the fundamentality of the area, the approach that underpins it, the key definitions of competences, capacities and performances, pedagogical processes, teaching processes of the area, evaluation techniques and tools, educational means and materials.